Stereoelectronic Control in the Ozone‐Free Synthesis of Ozonides - dos Passos Gomes, Gabriel; Yaremenko, Ivan A.; Radulov, Peter S.; Novikov, Roman A.; Chernyshev, Vladimir V.; Korlyukov, Alexander A.; Nikishin, Gennady I.; Alabugin, Igor V.; Terent'ev, Alexander O. (Angewandte Chemie International Edition, 2017)
The value of stereoelectronic guidelines is illustrated by the discovery of a convenient, ozone‐free synthesis of bridged secondary ozonides from 1,5‐dicarbonyl compounds and H2O2. The tetraoxane products generally formed in reactions of carbonyl and dicarbonyl compounds with H2O2 were not detected because the structural distortions imposed on the tetraoxacyclohexane subunit in [3.2.2]tetraoxanonanes by the three‐carbon bridge leads to the partial deactivation of anomeric effects. The new procedure is readily scalable to produce gram quantities of the ozonides. This reaction enables the selective preparation of ozonides without the use of ozone. Ozonides without the ozone: The synthesis of bridged secondary ozonides from 1,5‐dicarbonyl compounds and H2O2 was guided by stereoelectronic considerations (see scheme). The tetraoxane products usually formed under these conditions were not detected owing to the partial deactivation of anomeric effects as a result of distortion of the tetraoxacyclohexane subunit in the [3.2.2]tetraoxanonane intermediates by the three‐carbon bridge.